Philippine medical thesaurus on anatomy body regions - Siapno, Joanna O. (School of Library and Information Studies, University of the Philippines Diliman, 2003)
Realizing the need to organize medical information, a group of researchers decided to initiate the creation of a thesaurus. This idea led to the establishment of the Philippine Medical Thesaurus Project in collaboration with the Medical Informatics Unit (MIU) of the University of the Philippines Manila College of Medicine (UPMCM). It is a long-term project which will include a series of studies and will take years of completion. As such, this paper on `Body Regions' of Anatomy is one of the series. The language chosen was Tagalog since it was considered the best studied Philippine language.